Mathematics Anxiety and Undergraduate Nursing Students: A Mixed Methods Study - Jen Austerberry; Thomas Mathew; Jacqueline Johnston; Maria Murphy; Kolsoom Safari; Christine Murray; Lisa McKenna (Nursing Open)
ABSTRACT Background Sound mathematical skills are paramount for effective nursing practice and patient safety. Objectives To explore the factors that influence nursing student anxiety when engaging with mathematics‐related activities in nursing education. Design A concurrent mixed methods employing cross‐sectional online survey and focus group interviews. Setting One undergraduate nursing course at an Australian university. Participants Bachelor of Nursing students from across academic years. Methods An online survey comprising closed‐ and open‐ended questions to assess mathematics anxiety and self‐efficacy and associated factors affecting its application to practice. Focus group interviews to explore anxieties related to mathematics and students' approaches to nursing mathematics. Quantitative data were analysed using descriptive statistics and qualitative data using inductive content analysis. Results A total of 202 nursing students commenced the survey, of which 135 were fully completed, while 17 students participated in focus groups. Less than half were school leavers. Around three‐quarters reported some level of fear of mathematics, while many lacked confidence, fear of making errors and/or harming patients and negative childhood experiences of mathematics. Survey items demonstrated extensive variation in perceptions. Conclusions The complexity and diversity of anxieties presents key challenges for nurse academics seeking to educate competent, safe students. Teaching approaches should be varied and consideration of having specialist mathematics teachers and learning psychologists on teaching teams to ensure student success. Reporting Method This study is reported using Mixed Methods Reporting in Rehabilitation & Health Sciences (MMR‐RHS). Patient or Public Contribution No patient or public contribution.